2020
DOI: 10.3389/fnins.2020.589878
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intranasal Oxytocin on Neural and Behavioral Responses to Social Touch in the Form of Massage

Abstract: Manually-administered massage can potently increase endogenous oxytocin concentrations and neural activity in social cognition and reward regions and intranasal oxytocin can increase the pleasantness of social touch. In the present study, we investigated whether intranasal oxytocin modulates behavioral and neural responses to foot massage applied manually or by machine using a randomized placebo-controlled within-subject pharmaco-fMRI design. 46 male participants underwent blocks of massage of each type where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 135 publications
(187 reference statements)
4
12
0
Order By: Relevance
“…The STS is an important region for social cognition and may interact with the amygdala in the context of gaze following (Shepherd, 2010). Intranasal OXT enhances STS responses to emotional faces in females (Domes et al., 2010), during social touch in males (Chen et al., 2020) and making social judgments in autistic males and females (Gordon et al., 2013). Importantly OXT also increases resting‐state effective connectivity from the STS to the amygdala in both sexes (Jiang et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The STS is an important region for social cognition and may interact with the amygdala in the context of gaze following (Shepherd, 2010). Intranasal OXT enhances STS responses to emotional faces in females (Domes et al., 2010), during social touch in males (Chen et al., 2020) and making social judgments in autistic males and females (Gordon et al., 2013). Importantly OXT also increases resting‐state effective connectivity from the STS to the amygdala in both sexes (Jiang et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacologically, IAO can facilitate adaptive individuation/ categorization face-processing in men (Liu et al, 2021b), detection accuracy of briefly-presented emotional stimuli including facial emotion recognition (Schulze et al, 2011), and interpersonal synchrony during dance (Josef et al, 2019), but reduce the negative emotional impact of jealousy in established romantic partners and thus, help maintenance of positive inter-personal relationships (Zheng et al, 2021b). Consistently, IAO can increase the pleasantness of social touch massage and neural responses in key regions involved in reward, social cognition, emotion and salience and in default mode networks in men (Chen et al, 2020;Zheng et al, 2021a). In animal studies, the underlying neurochemical processes are further explored.…”
Section: Social Cognitionmentioning
confidence: 92%
“…Despite the challenges of reliably detecting BOLD signal in the amygdala [49,50], a few neuroimaging studies showed robust activation of the amygdala in response to affective touch. When the amygdala was activated by pleasant tactile stimuli, the BOLD signal was correlated with the perceived pleasantness of touch [51], likely because pleasurable tactile sensations activate the opioid system within the amygdala [52]. A subset of studies showed affective touch enhanced the functional connectivity between the amygdala and limbic cortical areas.…”
Section: Figure 1 Bottom-up and Top-down Touch-related Signals Converge In The Basal And Accessory Basal Nuclei Of The Primate Amygdala Tmentioning
confidence: 99%